2015
DOI: 10.2139/ssrn.2661492
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Relationships between Energy Consumption, CO2 Emissions and Economic Growth in 24 African Countries: A Panel ARDL Approach

Abstract: This study complements existing literature by examining the nexus between energy consumption (EC), CO 2 emissions (CE) and economic growth (GDP) in 24 African countries using a panel ARDL approach. The following findings are established. First, there is a long run relationship between EC, CE and GDP. Second, a long term effect from CE to GDP and EC is apparent, with reciprocal paths. Third, the error correction mechanisms are consistently stable. However, in cases of disequilibrium only EC can be significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
(22 reference statements)
5
30
0
1
Order By: Relevance
“…This negative impact has the potential to cause significant macroeconomic costs, as it interferes with production, consumption, and investment, and, therefore, defeats the leading economies goals of broader economic growth and development in the long run. We found that, the negative relationship between RGDP and OP is in line with Bouzid (2012), and Asongu et al (2015) empirical findings. The result argued that for leading African countries, an OP increase directly decreases real national income through lower export earnings.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…This negative impact has the potential to cause significant macroeconomic costs, as it interferes with production, consumption, and investment, and, therefore, defeats the leading economies goals of broader economic growth and development in the long run. We found that, the negative relationship between RGDP and OP is in line with Bouzid (2012), and Asongu et al (2015) empirical findings. The result argued that for leading African countries, an OP increase directly decreases real national income through lower export earnings.…”
supporting
confidence: 90%
“…The analysis revealed the negative effects of financial deepening on output growth in several sectors. While, Asongu et al (2015) found that, the energy consumption has a significant negative effect on economic growth, and there is a unidirectional relation is running from economic growth in energy consumption. Siddique and Majeed (2015) also showed that a feedback causality between economic growth and trade, and one-way causality running from financial development, trade to economic growth.…”
Section: Brief Of Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Environmental challenges such as global warming, acid rain and depletion of the ozone layer have often been associated with energy consumption (Sardianou, 2007;Asongu et al, 2016). Wuebbles and Jain (2001) found that the rising greenhouse gases can be attributed to the increased consumption of fossil fuels.…”
Section: Renewable Energy Policy Interventions In Ghanamentioning
confidence: 99%
“…This is because, the consumption of energy has been found to be a major determinant of CO 2 emissions (Bhattacharya, 2010;Asongu et al, 2016). This makes natural gas the ideal fuel choice.…”
Section: Introductionmentioning
confidence: 99%